(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Author analyses the problem of medically assisted suicide from the perspective of the philosophy of law, commenting critically the sentence of the Italian Constitutional Court. The focus is on the right to die and to live, letting die and killing, equality and non-discrimination, unbearable sufferance and self-determination; slippery slope, the role of physician and conscientious objection, the role of the ethical committees.